2008
DOI: 10.1016/j.bmcl.2008.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial selection of a single stranded DNA thioaptamer targeting TGF-β1 protein

Abstract: A phosphorothioate single-stranded DNA aptamer (thioaptamer) targeting transforming growth factor-β1 (TGF-β1) was isolated by in vitro combinatorial selection. The aptamer selection procedure was designed to modify the backbone of single-stranded DNA aptamers, where 5′ of both A and C are phosphorothioates since this provides enhanced nuclease resistance as well as higher affinity than that of a phosphate counterpart. The thioaptamer selected from a combinatorial library (5 × 10 14 sequences) binds to TGF-β1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 20 publications
(3 reference statements)
0
44
0
2
Order By: Relevance
“…An enormously well-fitting oligonucleotide can be selected from a library of thousands or millions compounds using a very powerful technique -in vitro combinatorial selection. Gorenstein and coworkers isolated in that way a phosphorothioate single-stranded DNA aptamer (thioaptamer) targeting transforming growth factor-b1 (TGF-b1) [179]. The protein suppresses the immune system, and inhibition of the TGF-b signaling pathway has been proposed for cancer therapy.…”
Section: Phosphorothioate Analogs [Mix-ps]- [All-(r P )-Ps]-and [Amentioning
confidence: 99%
“…An enormously well-fitting oligonucleotide can be selected from a library of thousands or millions compounds using a very powerful technique -in vitro combinatorial selection. Gorenstein and coworkers isolated in that way a phosphorothioate single-stranded DNA aptamer (thioaptamer) targeting transforming growth factor-b1 (TGF-b1) [179]. The protein suppresses the immune system, and inhibition of the TGF-b signaling pathway has been proposed for cancer therapy.…”
Section: Phosphorothioate Analogs [Mix-ps]- [All-(r P )-Ps]-and [Amentioning
confidence: 99%
“…335 G-quadruplex aptamers have been identified that inhibit the reverse transcriptases of many primate lentiviruses at low nanomolar concentration, 336 whilst a further aptamer (non-G-quadruplex structure) was found that could bind specifically to a known drugresistant mutant of HIV-1 RT (mutant 3) but not to the wild-type RT, and could therefore be used in diagnosis. 337 Aptamers have also been selected that bind the transforming growth factor-b1, 338 and to the transferring receptor. 339 Glycoproteins have also been targets for aptamer selection.…”
Section: Aptamers and (Deoxy)ribozymesmentioning
confidence: 99%
“…[157][158][159] Neben den Antikörpern werden verschiedene weitere zielführende Gruppen untersucht: Liganden, Aptamere und kleine Peptide, die spezifisch an Zelloberflächenmarker binden, oder an Oberflächenmar-ker, die in der Umgebung eines Krankheitsherds exprimiert werden. [160][161][162] Die zweite Unterklasse dieser Nanovektoren umfasst responsive Systeme, z. B. pH-empfindliche Polymere oder Systeme, die durch ortsspezifische Enzyme des Krankheitsherds aktiviert werden, ebenso wie verschiedene extern aktivierbare Vektoren.…”
Section: Aufsätze 898 Wwwangewandtedeunclassified